A representação da morte nas reportagens de capa da Revista VEJA - Bosco, Silvania Dal (2013)
The research analyzes the types of communicational contracts drafted by publishers of Veja magazine in their cover stories that had a death theme of various situations, in order to identify the interests that involve implicit or explicit strategies for building these texts. Based on the theoretical foundations of Ernesto Laclau and Norman Fairclough in their theories of discourse, seeks to understand generally, the dynamics of discursive practices in the weekly press, with emphasis on the discursive procedures that mobilizes Veja to establish communication contracts (Patrick Charaudeau ) with their readers. Discourse theory provides a foundation for understanding the intrinsic relationship between text and social context within social relations. In this horizon, on one hand, the research part of the central concepts supported by this theory, such as speech, nodal point in their connections with the communication contracts, which are part of the discursive articulations that the magazine embarks on its journalistic activity. On the other hand, it s understood that it is not possible to analyze the death without addressing the real trauma, which will be supported by the teachings of Slavo Zizek. The study has methodological bases of the discourse analysis in order to investigate the forms of organization of statements about death. These strategies enable the establishment of a fiduciary relationship between speaker and magazine reader, thus ensuring their loyalty. The body of the research comprises of the cover stories of Veja whose theme is the representation of death in the period from January 2000 to December 2010. The survey results indicate differences in the treatment of death of the same and the other, here and there, by the publisher. The organizational form of speech is based on oppositions that give reader the perception that in each type of death there are causes and culprits. This feature is materialized based on dichotomies that are presented in a battle between good and evil; between Same and Other; between East and West, between civilized and barbarian, between the developed and under developed